Victimological Developments in the World during the Past Three Decades (I): A Study of Comparative Victimology - Schneider, Hans Joachim (International journal of offender therapy and comparative criminology, 2001)
During the past three decades, 10 international symposia on victimology have taken place at the following locations: Jerusalem (1973); Boston (1976); Muenster, Germany (1979); Tokyo and Kyoto (1982); Zagreb, Croatia (1985); Jerusalem (1988); Rio de Janeiro (1991); Adelaide, Australia (1994); Amsterdam (1997); and Montreal (2000). In the two parts of this article, a comprehensive overview of the discussion results of these symposia and of the most important literature contributions to criminological victimization research over the past three decades will be presented. In the first part of this article, empirical victim research, international risk of victimization, and national risk in Germany will be discussed. Four groups of victims, serving as examples, will be analyzed in more detail: foreigners, women (rape), children (sexual abuse), and older persons (physical abuse). The causes of victimization will be explored: These comprise socialstructural, cultural, and institutional victimization. The concept of victim precipitation, the lifestyle-routine-opportunity model, and the routine-activity theory will be described